Virtual-reality simulator system for double interventional cardiac catheterization using haptic force producer with visual feedback. (July 2016) - Chen, Guan-Chun; Lin, Chia-Hung; Li, Chien-Ming; Hsieh, Kai-Sheng; Du, Yi-Chun; Chen, Tainsong
Abstract: Atrial septal defect is a serious congenital heart disease. Interventional cardiac catheterization has increasingly become a treatment for its correction, with reduced risks for infections and complications of anesthesia. However, the cardiac catheterization still poses a huge challenge for novice surgeons; therefore a double-catheter system is warrant for training surgeons. In this study, a novel mechanical training system is designed for interventional cardiac catheterization simulation. Visual and haptic feedback simulators were developed from medical records to simulate accidental bumps into the vessel walls. The results indicate that this proposed system could accurately simulate the resistance encountered during cardiac catheterization and achieve the desired training outcomes. This simulation module can be a potential of teaching platform for training surgeons in medical education.